Visual aspects in contemporary artistic mappings - Momberg Araujo, Gabriela; Manuel Reis Velloso, Leandro (InfoDesign, 2025)
This is an excerpt from a research project in the field of information design, which aims to identify visual principles in artistic mappings displayed in exhibition environments. The term “mapping” is used to define the practice in focus, which consists of spatializing data into material configurations. The study is based on an exploratory survey of contemporary projects in the field of the arts, through research into collections, compilations, artist and designer portfolios, and visits to exhibitions. The analysis is based on design research tools. The 11 categories found synthesize visual properties, which are presented and discussed in this article.